2022
DOI: 10.1002/mar.21737
|View full text |Cite
|
Sign up to set email alerts
|

Role of artificial intelligence in marketing strategies and performance

Abstract: This study examines the role of artificial intelligence (AI) as a marketing strategy and explains its contribution to firms and the factors influencing their development. The study tests an empirical model based on the research variables and constructs identified using structural equation modeling and the fuzzy set qualitative comparative analysis (FsQCA) approach. Data were collected from 278 food firms. The findings indicate that the implementation of an AI marketing strategy affects performance. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 85 publications
0
12
0
1
Order By: Relevance
“…Research by highlights the strategic application of AI in marketing, where different types of AI can be utilized at various stages of the marketing strategy process, such as segmentation, targeting, and positioning. Wu & Monfort (2022) emphasize that factors like marketing capabilities and customer co-creation positively influence AI marketing strategy and performance. Moreover, Ho & Chow (2023) point out that in AI marketing efforts, factors like information, accessibility, and customization can significantly impact brand experience.…”
Section: Factors Influencing the Relationship Between The Use Of Ai T...mentioning
confidence: 99%
“…Research by highlights the strategic application of AI in marketing, where different types of AI can be utilized at various stages of the marketing strategy process, such as segmentation, targeting, and positioning. Wu & Monfort (2022) emphasize that factors like marketing capabilities and customer co-creation positively influence AI marketing strategy and performance. Moreover, Ho & Chow (2023) point out that in AI marketing efforts, factors like information, accessibility, and customization can significantly impact brand experience.…”
Section: Factors Influencing the Relationship Between The Use Of Ai T...mentioning
confidence: 99%
“…Prior research has examined consumers' technology‐facilitated brand engagement in the context of technologies, including social media, virtual‐, augmented‐, or mixed reality applications, and automated or artificially intelligent technologies, among others (e.g., Puntoni et al, 2021), which have been demonstrated to boost corporate performance (Huang & Rust, 2021). Here, consumers’ engagement with artificially intelligent technologies—in particular, those able to perform tasks without human intervention (e.g., generative or predictive artificial intelligence [AI]; Dwivedi et al, 2023)—is receiving widespread attention in the consumer psychology and marketing literatures (Sampson, 2021; Wu & Monfort, 2023). Among these, the AI subclasses of machine learning (i.e., an AI subset, which uses algorithms that flexibly adapt to data constellations to improve task performance) and deep learning (i.e., a machine learning subset that involves computing multilayer neural networks) technologies are able to offer improved decisions or predictions over time based on the deployed (e.g., big) data (Hollebeek et al, 2021; Pradeep et al, 2019), thus offering consumers increasingly accurate (e.g., product) solutions (Leung et al, 2018), provided high‐quality training data and state‐of‐the‐art algorithms are used.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Artificial Intelligence (AI) finds increasing application for sales forecast and price or revenue prediction problems and optimization. To date, a wave of AI point solutions has been proposed (Agrawal et al, 2022), but only few studies provide a structured framework for AI decisions in marketing (Wu and Monfort, 2022), and to the best of our knowledge, there is no comparative assessment of existing AI support for concrete use cases in price management. Several classification criteria of AI systems have been used (by type of AI, industry usage, mode of human-AI cooperation, primary role of AI, etc.)…”
Section: Introductionmentioning
confidence: 99%